Exploring the Absurdity of War: A Literary Analysis of Catch-22 - Neziri, Anita; Turku, Marsela; Pavlíková, Martina (Journal of Education Culture and Society, 2024)
Aim. This study aims to conduct a comprehensive analysis of the absurdities inherent in combat events as depicted in Joseph Heller's novel, Catch-22. The study seeks to explore how Heller utilizes literary techniques such as sarcasm, black humor, and surrealism to portray the contradictions, irrationality, and overall absurd nature of war. Additionally, the study aims to unfold the deeper societal implications, including dehumanization and moral degradation, presented in the novel.Method. The research method employed in this study is primarily a qualitative literary analysis. The analysis involves a close examination of the text of Catch-22, focusing on the novel's characters, plot structure, narrative techniques, and the use of literary devices. It engages in critical interpretation and evaluation of how Heller employs sarcasm, black humor to convey the absurdities of war.Results. The study reveals that Joseph Heller employs a unique set of literary techniques, including non-sequential narrative, broken chronology, and cyclical motifs, to vividly capture the chaotic and absurd nature of combat events.The analysis uncovers recurring themes such as bureaucratic absurdities, loss of personal agency, dehumanization, and the existential toll of war. The study highlights the significance of the Catch-22 paradox as a central motif, illustrating the circular and illogical nature of bureaucratic processes during war.Conclusion. Joseph Heller's Catch-22 serves as a powerful critique of the absurdities prevalent in wartime. The Catch-22 paradox emerges as a symbolic representation of bureaucratic folly, encapsulating the struggle of individuals caught in the machinery of conflict.